2009
DOI: 10.1002/bjs.6438
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of insulin-like growth factor II mRNA-binding protein 3 expression in gastric adenocarcinoma

Abstract: IMP-3 expression correlates with the metastatic potential of gastric adenocarcinoma and is an independent prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
3
23
1
Order By: Relevance
“…S1) according to published reports. (22,23) The staining results were evaluated by a pathologist (Y.M.J.) who was blind to the clinical background of the specimens.…”
Section: Methodsmentioning
confidence: 99%
“…S1) according to published reports. (22,23) The staining results were evaluated by a pathologist (Y.M.J.) who was blind to the clinical background of the specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 outlines the reported frequencies of IMP3 expression in human malignancies, either by immunohistochemistry or reverse transcription polymerase chain reaction (RT-PCR) studies. IMP3 is expressed in a variety of tumors with variable positivity, including pancreatic adenocarcinoma, esophageal adenocarcinoma, melanoma, gallbladder carcinoma, serous endometrial carcinoma, Hodgkin lymphoma, pulmonary and extrapulmonary small cell carcinoma, pulmonary large cell neuroendocrine carcinoma, Merkel cell carcinoma, hepatocellular carcinoma, cholangiocarcinoma, colorectal adenocarcinoma, gastric adenocarcinoma, ovarian carcinoma, non-small cell lung cancer, follicular thyroid carcinoma, laryngeal squamous cell carcinoma, renal cell carcinoma, urothelial carcinoma of the bladder, osteosarcoma, malignant pleural mesothelioma, meningioma, pituitary adenoma, and pituitary carcinoma [6,9,[11][12][13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52]…”
Section: Introductionmentioning
confidence: 99%
“…High levels of IMP3 expression have been reported to have diagnostic and/or prognostic value in different malignant tumors (kidney, ovary, liver, endometrium, esophagus, biliary tract, bladder, uterine cervix, stomach, colonrectum, esophagus, lung, exocrine pancreas, thyroid, ovary, testis, bone, and skin) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 2). Our results confirmed the expression of IMP3 in the normal pituitary tissues, previously reported, using immunohistochemical, Western blotting, and RT-PCR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IMP3 is associated with aggressive and advanced carcinomas in colon, kidney, neuroendocrine skin (Merkel cell carcinoma), liver, bladder, ovary, and in soft tissue sarcomas [16][17][18][19][20][21][22][23][24][25]. On the basis of these results, IMP3 may be a useful prognostic factor in many malignant solid tumors.…”
Section: Introductionmentioning
confidence: 97%